HUBUNGAN TINGKAT PENGETAHUAN TENTANG DIET PURIN DENGAN KADAR ASAM URAT PADA PRIA KAUM BAPA GEREJA DI DESA KUWIL - Tumbel, Ean Julia; Kairupan, Carla; Sembiring, Erika (JURNAL KEPERAWATAN, 2024)
Background Increased levels of uric acid in the blood are often known as hyperuricemia. Limiting the consumption of foods and drinks that contain purines, is determined by the level of knowledge of a person related to the purine diet. The aim This study aims to determine the relationship between the level of knowledge about the purine diet and uric acid levels in Men of the Church in Kuwil Village. The method With a cross sectional research design and using a questionnaire on the level of knowledge of the purine diet and examination of uric acid levels using the Autocheck examination tool. The research sample consisted of 40 respondents who were obtained using the accident sampling technique and bivariate analysis using chi square test. The results The study showed 62.5% of respondents had a low level of knowledge related to the purine diet and 57.5% of respondents experienced an increase in uric acid levels. The results of the chi square test obtained P-value = 0.000 (< = 0.05). The conclusion Results of this study indicate that there is a relationship between the level of knowledge about the purine diet and uric acid levels in Men of the Church in Kuwil Village. Keywords: Knowledge; Purine Diet; Uric Acid.